Economie analysis of pavement layers according to AASHTO-86 method - Kök, Baha Vural; Kulo?lu, Necati (My University, 2007)
In AASHTO-86 design method, the structural number (SN) is determined in respect of bearing capacity of subgrade, total standard equivalent axle load, reliability level, standard deviation and serviceability index because of the structural number have to be equal and bigger than the sum of the coefficient that is multiplied with layer thickness and drainage factor a lot of combination occurs. In this study 441000 alternative occurred from the different values of parameter placed in design criterion have been analyzed according to AASHTO-86 method by using MATLAB program. In conclusion the economic thickness of layers forming pavement for different equivalent axle load number, the effect of the bearing capacity of subgrade on pavement cost, the mathematical relation between axle load number, bearing capacity and cost of pavement and the most suitable and economic base and subbase type have been determined.
AASHTO-86 yöntemine göre üstyapi tabakalarinin ekonomik analizi
Keywords: AASHTO-86 method; Bearing capacity; Economic analysis; Pavement layers